(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes how cellulose solvents affect cellulose in our country, what solvents affect cellulose, what has been done in this regard, how to identify and use the most effective and harmless solvents, that the most common type of cellulose, that cellulose is composed of β-glucopyranose, that cellulose has a strict linear structure, that cellulose does not dissolve or vaporize, that cellulose decomposes, and under what conditions experiments should be conducted